Application of social stories in working with children with autism spectrum disorder: comparison of the perceptions of teachers and parents - Milićević, Sara (Norma, 2023)
Autism spectrum disorders (ASDs) represent a group of neurodevelopmental disorders characterized by deficits in social communication and interaction, and the presence of limited, repetitive patterns of behavior, interests or activities in early development, which negatively affects a person's development in all domains. As deficits in social interaction significantly complicate the adaptation of persons with PSA to the environment, and social skills cannot be learned spontaneously, it is necessary to apply different interventions. Social stories are recommended in working with people with PSA, although it must be pointed out that the results of research on the effectiveness of this intervention are conflicting. As teachers and parents play a significant role in a child's life, and often perceive the child's behavior in different ways, the paper was written with the aim of comparing the experiences of teachers and parents in the application of social stories in children with PsA. Based on the analysis of the included literature, which was accessed through the Google Scholar electronic search engine, it can be concluded that teachers and parents share opinions about the positive effect of social stories in the domain of behavior and social skills of children with PSA. It would be significant if, in future research on the topic of evaluating the application of this intervention, apart from objective factors that indicate changes in the child's behavior, the opinions of parents and teachers are also taken into account during the evaluation, in order to gain a realistic insight into the effectiveness of this intervention, and that its content and method of use would eventually be improved.
Keywords: autism spectrum disorders; social stories; social skills; teachers' experiences; parents' experiences